The leadership habitus of principals in elite contexts: an exploration of practice in four schools - MacMahon, Anna (School of Education, 2014)
The purpose of this study is to describe and compare leadership practices in four elite schools, in order to investigate the relationship between the practices of school leaders, their histories and the contexts in which they lead.